Plastome phylogenomics and historical biogeography of aquatic plant genus Hydrocharis (Hydrocharitaceae) - Li Zhi‑Zhong; Lehtonen Samuli; Gichira Andrew W.; Martins Karina; Efremov Andrey; Wang Qing‑Feng; Chen Jin‑Ming (BioMed Central, 2022)
Background Hydrocharis L. and Limnobium Rich. are small aquatic genera, including three and two species, respectively. The taxonomic status, phylogenetic relationships and biogeographical history of these genera have remained unclear, owing to the lack of Central African endemic H. chevalieri from all previous studies. We sequenced and assembled plastomes of all three Hydrocharis species and Limnobium laevigatum to explore the phylogenetic and biogeographical history of these aquatic plants. Results All four newly generated plastomes were conserved in genome structure, gene content, and gene order. However, they differed in size, the number of repeat sequences, and inverted repeat borders. Our phylogenomic analyses recovered non-monophyletic Hydrocharis. The African species H. chevalieri was fully supported as sister to the rest of the species, and L. laevigatum was nested in Hydrocharis as a sister to H. dubia. Hydrocharis-Limnobium initially diverged from the remaining genera at ca. 53.3 Ma, then began to diversify at ca. 30.9 Ma. The biogeographic analysis suggested that Hydrocharis probably originated in Europe and Central Africa. Conclusion Based on the phylogenetic results, morphological similarity and small size of the genera, the most reasonable taxonomic solution to the non-monophyly of Hydrocharis is to treat Limnobium as its synonym. The African endemic H. chevalieri is fully supported as a sister to the remaining species. Hydrocharis mainly diversified in the Miocene, during which rapid climate change may have contributed to the speciation and extinctions. The American species of former Limnobium probably dispersed to America through the Bering Land Bridge during the Miocene.